SURFACE MODIFIED NANOPARTICLES FOR EOR APPLICATIONS - Lam, Jen Hui (Universiti Teknologi PETRONAS, 2016)
These days, due to the high demand of crude oil and the depletion of it, many oil companies have started to explore more ways to recover the original oil in place (OOIP) as much as possible. Enhanced oil recovery (EOR) is being known as a tertiary recovery method which is being applied after primary and secondary methods take placed. EOR is being massively studied and applied in the oil industry. There are mainly three types of EOR which are gas EOR, water-based EOR and thermal EOR. Due to oil’s nature in being highly vicious, it is difficult to use flooding methods, for instance water alternating gas or foam water alternating gas.